KONDISI VEGETASI DAN PANDUAN INISIASI RESTORASI EKOSISTEM HUTAN DI BEKAS AREAL KEBAKARAN BUKIT POHEN CAGAR ALAM BATUKAHU BALI (SUATU KAJIAN PUSTAKA) - -, SUTOMO (Jurnal Biologi Udayana; Vol 13 No 2 (2009): JURNAL BIOLOGI, 2009)
Forest fire in 1994 has destroyed some areas in Pohen’s hill Batukahu nature reserve. Ecological restoration is needed to be initiated. To gain information on vegetation condition needed to design a suitable restoration model a field survey was conducted. Result showed that secondary succession is progressing in this area. Pioneer species such as Eupatorium, Melastoma and Homalathus were found here. Local species (Dacrycarpus imbricatus) that has an important value was also found escaped from the severe forest fire. An integrated restoration concept is proposed to help initiating the ecosystem rehabilitation.
Keywords: Ecosystem restoration, Pohen’s hill, Batukahu Nature Reserve Bali